Ground Settlement Due to Tunneling in Cohesionless Soil - Mohammad Faraz Athar; Md Rehan Sadique; Abdullah H. Alsabhan; Shamshad Alam (Applied Sciences, 2022)
By the year 2035 it is estimated that Delhi and Mumbai will become two of the most populous cities around the globe. The massive population growth rate has led to the rise of land scarcity, urbanization, and industrialization and developments for rapid transit systems have made accordingly. Modern rapid transit systems comprise Metro rails and subways etc., and increase underground-construction activities. Nowadays, the tunnel-construction process heavily relies on massive machineries such as tunnelling-boring machines (TBM) and operations that produce great hindrance in the soil mass resulting in ground settlement at the surface. This study aimed to address these issues through small-scale laboratory experiments and further amplification to real-valued problems utilizing numerical methods. A cubic box of edge length 1 m made up of mild steel was generated to simulate a tunnelling operation and aluminum-made lining were used to simulate concrete tunnel linings. A finite element-based numerical investigation was done for a 2D elastoplastic numerical tunnel model with dimensions of 42 m × 42 m. Analysis was carried out on Optum G2 software. The analyzed variations in lining shapes of lining included circular, horseshoe, arch, elliptical, and square. Results showed that elliptical-shaped linings experienced the least ground settlement and these are recommended for places where surface settlement may cause major damage. It is also recommended that square-shaped linings should not be used in such situations due their higher settlement values.